KUSA-A1 mesenchymal stem cells response to PEEK-Si3N4 composites. (September 2020) - Marin, E.; Boschetto, F.; Zanocco, M.; Adachi, T.; Toyama, N.; Zhu, W.; McEntire, B.J.; Bock, R.M.; Bal, B.S.; Pezzotti, G.
Abstract: Poly-Ether-Ether-Ketone (PEEK) is a structural biopolymer with various biomedical applications, from spinal cages to dental prosthetics. Due its high chemical stability combined with good mechanical strength, PEEK is considered to be one of the most successful bio-inert polymers ever developed. In this work, a mixture of PEEK and β -Si3 N4 was used to produce a composite material which combined the mechanical properties of the polymer with the bioactive effects of a reinforcing ceramic, in particular its good osteoconductivity. When tested with KUSA-A1 mesenchymal cells, the composite material resulted in a higher production of bone tissue when compared to standard PEEK or biomedical titanium alloy. On the other hand, the composite showed poor osteogenic differentiation as evaluated by ALP. Tests performed using various spectroscopic techniques showed that the bone tissue formed has a balanced mineral-to-matrix ratio, similar to that of healthy bone tissue. Highlights: Si3N4 has been successfully used as a reinforcing particle into medical grade PEEK polymers. While PEEK inhibits osteogenic differentiation of mesenchemyal cells, Si3N4 promotes it. Si3N4 particles induce higher formation of bone tissue on the composite material.